Design, Automation &Amp; Test in Europe Conference &Amp; Exhibition (DATE), 2014 2014
DOI: 10.7873/date.2014.052
|View full text |Cite
|
Sign up to set email alerts
|

On the assumption of mutual independence of jitter realizations in P-TRNG stochastic models

Abstract: International audienceSecurity in true random number generation in cryptography is based on entropy per bit at the generator output. The entropy is evaluated using stochastic models. Several recent works propose stochastic models based on assumptions related to selected physical analog phenomena such as noise or jittery signal and on the knowledge of the principle of randomness extraction from the obtained analog signal. However, these assumptions simplify often considerably the underlying analog processes, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…In particular, we want to obtain a number of oscillations close to 100. With such a number of oscillations, we can assume that their variation comes mainly from the thermal noise inside transistors and that the realizations of the counter values are independent as it was shown in [4]. Indeed, we observed that for a significantly smaller number of oscillations the accumulated entropy was insufficient and for a number of oscillations too high the jitter coming from the flicker noise could cause the dependence between subsequent output samples to be non-negligible.…”
Section: Implementation Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…In particular, we want to obtain a number of oscillations close to 100. With such a number of oscillations, we can assume that their variation comes mainly from the thermal noise inside transistors and that the realizations of the counter values are independent as it was shown in [4]. Indeed, we observed that for a significantly smaller number of oscillations the accumulated entropy was insufficient and for a number of oscillations too high the jitter coming from the flicker noise could cause the dependence between subsequent output samples to be non-negligible.…”
Section: Implementation Resultsmentioning
confidence: 57%
“…Consequently, n(t) can be represented as a stationary Gaussian random process. 4 Let us now analyze variations in the width of the pulse transmitted over one inverter as explained earlier in this section, but now in the presence of noisy currents. Let us consider that at t = t ↑ , signal V in goes up from V GND to V CC , and we denote t a the time, at which the signal V out at the output of the inverter reaches (…”
Section: Modeling a Noisy Invertermentioning
confidence: 99%
“…To compare the parameters of the proposed randomness monitoring process, we implemented tests based on counter differences and two other state-of-the-art tests (proposed in [HBFT14] and [FL14]) in the same device -Intel Cyclone V FPGA.…”
Section: Implementation Of the Variance Measurements In Hardware And mentioning
confidence: 99%
“…The circuitry corresponding to hardware implementation of the variance computation used by Haddad et al in [HBFT14] and for the one corresponding to Eq. (2) is depicted in Fig.…”
Section: Implementation Of the Variance Measurements In Hardware And mentioning
confidence: 99%
See 1 more Smart Citation